2014
DOI: 10.1038/ncomms4396
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative live-cell imaging reveals spatio-temporal dynamics and cytoplasmic assembly of the 26S proteasome

Abstract: The 26S proteasome is a 2.5-MDa multisubunit protease complex that degrades polyubiquitylated proteins. Although its functions and structure have been extensively characterized, little is known about its dynamics in living cells. Here, we investigate the absolute concentration, spatio-temporal dynamics and complex formation of the proteasome in living cells using fluorescence correlation spectroscopy. We find that the 26S proteasome complex is highly mobile, and that almost all proteasome subunits throughout t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
123
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(141 citation statements)
references
References 61 publications
15
123
3
Order By: Relevance
“…Recent fluorescence correlation spectroscopy studies also support the conclusion that proteasomes can be imported into the nucleus as holo-enzymes ( Pack et al , 2014; Figure 3). However, the maturation state of the GFP-labelled proteasomes was unclear.…”
Section: Discussion/analysis Of the Literaturementioning
confidence: 60%
“…Recent fluorescence correlation spectroscopy studies also support the conclusion that proteasomes can be imported into the nucleus as holo-enzymes ( Pack et al , 2014; Figure 3). However, the maturation state of the GFP-labelled proteasomes was unclear.…”
Section: Discussion/analysis Of the Literaturementioning
confidence: 60%
“…We did not detect intact proteasomes in the nucleus, and virtually all peptidase activity was present in the cytosol. These findings diverge from the general opinion, which maintains that proteasomes degrade proteins inside the nucleus (4,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Our results predict an important regulatory role for export in the degradation of nuclear proteins.…”
contrasting
confidence: 56%
“…All proteasome activity that was applied to the column was recovered in these fractions, and none was detected in the trailing column fractions. Because proteasome subunits are present predominantly in intact complexes in vivo (18), the weak 20S, specific activity observed in fractions 16 and 17, could reflect post-lysis dissociation of the 26S proteasome. The fractionated proteins were examined by immunoblotting, and 20S subunits (␣4, ␤7) were found in all fractions that contained peptidase activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although it was shown that CP and RP components are imported separately into the nucleus, a recent study demonstrated that the 26S proteasome completes its assembly process in the cytoplasm and is able to enter the nucleus as a holocomplex (Pack et al, 2014). Thus, although XopJ itself is not a nuclear protein, its interference with proteasome assembly outside the nucleus eventually inhibits proteasome activity in the cytoplasm as well as in the nucleus, because it prevents the nuclear import of functional proteasome complexes.…”
Section: Discussionmentioning
confidence: 99%